Validitas Soal Matematika Tipe PISA Konteks Covid-19 - Sintia Andita; Liana Septy; Harisman Nizar; Rieno Septra Nery (JEMST (Jurnal of Education in Mathematics, Science, and Technology), 2020)
This study was carried out to test the validity of math problems in Al-Hijrah High School 10th grade students with a maximum age of 15 year. The goal of this study was to obtain the most recent PISA type math questions in the context of Covid-19 with an accurate level of validity as determined by expert review and one-to-one. The trial was conducted on three students with different abilities in the classroom while still applying health protocols. This research was conducted through a development method that was divided into two stages, namely preliminary and formative evaluation, which included self-evaluation and prototyping (expert review and one-to-one). This research produces instrumen kits, namely grids, scoring rubrics, question cards and of course the prototype 2 question sets that are feasible to use. Keyword: PISA, Expert Review, One-to-one, Mathematics